To solve the system of equations by combining them, we will first rewrite the two equations:
-
\( -2x - 7y = -14 \) (Equation 1)
-
\( -x - 5y = -13 \) (Equation 2)
Next, we can manipulate these equations to eliminate one of the variables. Let's first multiply Equation 2 by 2 to align the coefficients of \( x \):
\[ 2(-x - 5y) = 2(-13) \]
This gives us:
\[ -2x - 10y = -26 \quad (Equation 3) \]
Now we have the system:
-
\( -2x - 7y = -14 \)
-
\( -2x - 10y = -26 \)
Now we can eliminate \( -2x \) from both equations. We do this by subtracting Equation 1 from Equation 3:
\[ (-2x - 10y) - (-2x - 7y) = -26 - (-14) \]
This simplifies to:
\[ -10y + 7y = -26 + 14 \]
So, we get:
\[ -3y = -12 \]
Now, divide both sides by -3:
\[ y = 4 \]
Now that we have \( y \), we can substitute it back into one of the original equations to find \( x \). Let's substitute \( y = 4 \) into Equation 1:
\[ -2x - 7(4) = -14 \]
This simplifies to:
\[ -2x - 28 = -14 \]
Adding 28 to both sides gives:
\[ -2x = 14 \]
Dividing by -2, we find:
\[ x = -7 \]
So, the solution to the system of equations is:
\[ x = -7, \quad y = 4 \]
The final answer is:
\[ (x, y) = (-7, 4) \]